Hydrogen peroxide priming modulates abiotic oxidative stress tolerance: insights from ROS detoxification and scavenging - Hossain, Mohammad A.; Bhattacharjee, Soumen; Armin, Saed-Moucheshi; Qian, Pingping; Xin, Wang; Li, Hong-Yu; Burritt, David J.; Fujita, Masayuki; Tran, Lam-Son P. (Frontiers in Plant Science, 2015)
Plants are constantly challenged by various abiotic stresses that negatively affect growth and productivity worldwide. During the course of their evolution, plants have developed sophisticated mechanisms to recognize external signals allowing them to respond appropriately to environmental conditions, although the degree of adjustability or tolerance to specific stresses differs from species to species. Overproduction of reactive oxygen species (ROS) (hydrogen peroxide, H2O2; superoxide, O2ˉ˙; hydroxyl radical, OH. and singlet oxygen, 1O2) is enhanced under abiotic and/or biotic stresses, which can cause oxidative damage to plant macromolecules and cell structures, leading to inhibition of plant growth and development, or to death. Among the various ROS, freely diffusible and relatively long-lived H2O2 acts as a central player in stress signal transduction pathways. These pathways can then activate multiple acclamatory responses that reinforce resistance to various abiotic and biotic stressors. To utilize H2O2 as a signaling molecule, non-toxic levels must be maintained in a delicate balancing act between H2O2 production and scavenging. Several recent studies have demonstrated that the H2O2-priming can enhance abiotic stress tolerance by modulating ROS detoxification and by regulating multiple stress-responsive pathways and gene expression. Despite the importance of the H2O2-priming, little is known about how this process improves the tolerance of plants to stress. Understanding the mechanisms of H2O2-priming-induced abiotic stress tolerance will be valuable for identifying biotechnological strategies to improve abiotic stress tolerance in crop plants. This review is an overview of our current knowledge of the possible mechanisms associated with H2O2-induced abiotic oxidative stress tolerance in plants, with special reference to antioxidant metabolism.